Predicting schizophrenia: findings from the Edinburgh High-Risk Study. - Johnstone, E; Ebmeier, K; Miller, P; Owens, D; Lawrie, S (2005)
BACKGROUND: The hypothesis that schizophrenia is neurodevelopmental was investigated in a prospective study of young people with a postulated 10-15% risk for the development of schizophrenia. AIMS: To determine premorbid variables distinguishing high-risk people who will go on to develop schizophrenia from those who will not. METHOD: A high-risk sample of 163 young adults with two relatives with schizophrenia was recruited. They and 36 controls were serially examined. Baseline measures were compared between those who did develop schizophrenia, a well control group, a well high-risk group and high-risk participants with partial or isolated psychotic symptoms. RESULTS: Of those at high risk, 20 developed schizophrenia within 2(1/2) years. More experienced isolated or partial psychotic symptoms. Those who developed schizophrenia differed from those who did not on social anxiety, withdrawal and other schizotypal features. The whole high-risk sample differed from the control group on developmental and neuropsychological variables. CONCLUSIONS: The genetic component of schizophrenia affects many more individuals than will develop the illness, and partial impairment can be found in them. Highly significant predictors of the development of schizophrenia are detectable years before onset.